Criteria and Methods of the Evaluation of the Student’s Musical-Creative Development at the Stage of Higher Education - Irina V. Cheremisova (Kurysheva) (Rossijskij psihologičeskij žurnal., 2016)
Since the graduate should have a number of professional competencies, as well as a high level of general culture, intelligence, creativity, and spirituality, the development of criteria and methods of the evaluation of the student’s musical-creative development in the educational process of the university is of particular relevance. The authors assert that the use of the developing potentials of music is situational and fragmented in the domestic system of higher education. Regardless of the traditions of pre-revolutionary education in Russia, mass music education ends in adolescence. According to the authors the secondary musical personality of the future specialist is the result of the continuing mass musical education of the person. The theoretical analysis of researches in this eld showed that various scientists noted vast possibilities of music when developing value guidelines in youth, nding the meaning of life and professional activity, for creative self-actualization, self-discovery, and spiritual communion. At the same time, the diagnostics of the musical and creative development of personality in psycho-pedagogical science remains a challenge by virtue of the complexity and many-sided nature of these phenomena. This problem is especially urgent when evaluating the eectiveness of programs of psychological support of the creative development of the student’s personality. This paper introduces the author’s aesthetic-semiotic approach to studying this issue. To evaluate changes in student’s personality in experimental study, the authors developed criteria, characteristics, and corresponding levels of the development of the secondary musical personality.